2011
DOI: 10.1089/lrb.2011.0005
|View full text |Cite
|
Sign up to set email alerts
|

Increased Lymphangiogenesis and Hemangiogenesis in Infant Cornea

Abstract: Background: Corneal lymphangiogenesis (LG) and hemangiogenesis (HG) accompany many diseases after inflammatory, infectious, traumatic or chemical insults. They also contribute to transplant rejection. It is known that corneal transplants in infants or children have a higher rejection rate than in adults. However, it has never been studied whether infant corneas differ from adult corneas in inflammatory LG, HG, or both, which is the focus of this study. Methods and Results: Corneal inflammatory LG and HG were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Data from Hajrasouliha et al [62] demonstrated a spatially distinct outgrowth pattern of blood and lymphatic vessels induced via bFGF-pellets. Distinct changes for lymph vessels but not blood vessels were also found between 3-week-old and 8-week-old mice: whereas lymphatic vessels of C57BL/6 mice exhibited an increase in the vessel calibre during ageing, the blood vessels retained their diameter [63]. Distinct changes for lymph vessels but not blood vessels were also found between 3-week-old and 8-week-old mice: whereas lymphatic vessels of C57BL/6 mice exhibited an increase in the vessel calibre during ageing, the blood vessels retained their diameter [63].…”
Section: Interdependence Of Angiogenesis and Lymphangiogenesismentioning
confidence: 88%
“…Data from Hajrasouliha et al [62] demonstrated a spatially distinct outgrowth pattern of blood and lymphatic vessels induced via bFGF-pellets. Distinct changes for lymph vessels but not blood vessels were also found between 3-week-old and 8-week-old mice: whereas lymphatic vessels of C57BL/6 mice exhibited an increase in the vessel calibre during ageing, the blood vessels retained their diameter [63]. Distinct changes for lymph vessels but not blood vessels were also found between 3-week-old and 8-week-old mice: whereas lymphatic vessels of C57BL/6 mice exhibited an increase in the vessel calibre during ageing, the blood vessels retained their diameter [63].…”
Section: Interdependence Of Angiogenesis and Lymphangiogenesismentioning
confidence: 88%
“…Lymphatic density in the perilimbal bulbar conjunctival area was graded and analyzed using the NIH Image J software, as described previously [ 21 ]. Basically individual lymphatic vessels in the defined area were highlighted and added together to generate a density score measured in pixels for each sample analyzed.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were performed according to our standard protocol. [14][15][16] Briefly, freshly excised wholemount corneas at day 14 after suture placement were fixed in acetone for immunofluorescent staining against LYVE-1, CD31, F4/80, as reported previously. [14][15][16] For Ang-2 staining, the samples were stained with purified goat-anti-mouse Ang-2 antibodies, visualized by the Cy3-conjugated donkey-anti-goat or FITC-conjugated donkey-anti-goat secondary antibodies.…”
Section: Corneal Immunofluorescent Microscopy and Slit-lamp Biomicroscopymentioning
confidence: 99%
“…[14][15][16] Briefly, freshly excised wholemount corneas at day 14 after suture placement were fixed in acetone for immunofluorescent staining against LYVE-1, CD31, F4/80, as reported previously. [14][15][16] For Ang-2 staining, the samples were stained with purified goat-anti-mouse Ang-2 antibodies, visualized by the Cy3-conjugated donkey-anti-goat or FITC-conjugated donkey-anti-goat secondary antibodies. Samples were covered with mounting medium (Vectashield; Vector Laboratories, Burlingame, CA, USA) and digital images were taken by an epifluorescence microscope with software (AxioImager M1 with AxioVision 4.8; Carl Zeiss AG, Gottingen, Germany).…”
Section: Corneal Immunofluorescent Microscopy and Slit-lamp Biomicroscopymentioning
confidence: 99%